Proportional Intuitionistic Fuzzy AHP&VIKOR Methodology for Evaluating Telecommunications Service Providers in Post-Disaster Situations - Kadikoylu, Seren; Demir, Zeynep Burcu Kizilkan; Gul, Alize Yaprak; Sahin, Gulsah; Demir, Melisa Caliskan; Tekin, Ahmet Tezcan (OLD CITY PUBLISHING INC, 2026)
Disasters are recurring events worldwide, and in the absence of the necessary assistance following the event, the number of fatalities and property losses can increase significantly. In such circumstances, the establishment of a robust communications network is imperative for the effective dissemination of information, the coordination of rescue teams, and the implementation of appropriate responses. This study addresses the selection of a post-disaster telecommunications service provider and proposes a new Proportional Intuitionistic Fuzzy AHP&VIKOR methodology for this purpose. Within the paradigm of Proportional Intuitionistic Fuzzy Sets, the membership, non-membership and hesitation degree values, which are considered together in Intuitionistic Fuzzy Sets, are expressed through the utilization of proportions. This approach provides decision makers with the opportunity to represent values in a more accurate and understandable way. In the study, the most suitable telecommunications service provider is determined using the proposed methodology and a comparative analysis between Pro portional Intuitionistic Fuzzy AHP&EDAS and the proposed methodology is performed and the results are evaluated.
Keywords: Proportional Intuitionistic Fuzzy Sets; AHP; VIKOR; Post-Disaster Situations; Telecommunications Service Providers' Evaluation; CRITICAL SUCCESS FACTORS; SUPPLY CHAIN MANAGEMENT; OPERATORS; BARRIERS; CONTEXT; Computer Science; Science & Technology - Other Topics